Design, synthesis and DNA/RNA binding studies of nucleic acids comprising stereoregular and acyclic polycarbamate backbone: polycarbamate nucleic acids (PCNA) - Madhuri, Vangala; Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2010)
The designed, chiral, acyclic polycarbamate nucleic acids (PCNA) exhibited sequence and orientation specific binding to nucleic acids. Complexes of PCNA with DNA were as stable as PNA:DNA complexes and those with RNA were as stable as natural DNA:RNA complexes.